Implementasi Seorang Penabur Bagi Umat Kristen di Era Postmodern: Kajian Teologis Markus 4:1-20 - Yuslina Halawa; Surimawati Laia; Malik Bambangan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
in facing the changes in culture, thought, and morality that have emerged in the midst of postmodern society. In this context, Mark 4:1-20, which contains the parable of the sower, provides important insights into how the word of God The implementation of a sower for Christians in the postmodern era is a relevant topic to study considering the complex challenges faced by the church and individual Christians are delivered and received in various conditions of the human heart. This study aims to examine the relevance of the teachings in the parable for Christians in the postmodern era. In the postmodern era, where relativism, pluralism, and skepticism towards absolute truth are increasingly growing, the parable of the sower provides an illustration of how the word of God is spread and received in various situations. Just as the sower sows seeds into various types of soil (roadside soil, rocky soil, thorny soil, and fertile soil), so too Christians are faced with varying conditions of heart and mind in receiving the message of the gospel. This study identifies the challenges faced by the church, such as the influence of social media, individualism, and relativism, which can affect the way the word of God is received by postmodern society. Through a theological approach to Mark 4:1-20, this study offers a perspective on how Christians can act as faithful sowers, seeking to sow the seeds of the word with patience, and seeking to respond to various social and cultural conditions that exist wisely. Thus, the implementation of the parable of the sower in the context of the postmodern era not only invites people to actively spread the gospel, but also to understand the various challenges and heart situations that can affect the reception of the word.